P120 Comparison of cellular inflammation and TLR expression profiles between healthy and COPD subjects. (2nd December 2011) - Keys, A; Wilkinson, T; Staples, K J; North, M; Pink, S; Wilson, S; Kilty, I; Djukanovic, R; Nicholas, B
Abstract : Introduction and Objectives: Chronic obstructive pulmonary disease (COPD) is a complex inflammatory disease of the lungs Initiated by inhalation of toxic particles or gases. Periodic exacerbations triggered by respiratory pathogens are a major cause of morbidity/mortality in these patients. Microbial pathogens are recognised by pattern recognition receptors such as the toll-like receptors (TLRs), initiating innate immune defences. We hypothesised that abnormal TLR expression, and not resident inflammatory cell load in the lung parenchyma, contributes to exacerbation in COPD. Methods: Human lung tissue, distant from tumour margins, was taken from ex-smoker patients undergoing lobectomy for lung cancer. Patients were classified according to GOLD guidelines as healthy control subjects (HC) or those with COPD. Resected tissue was digested and cells analysed by flow cytometry for phenotypic markers of epithelial cells and inflammatory cell subtypes (macrophages, CD8+ and CD8− T lymphocytes) and the TLR2 and four expressions on these subtypes. Quantitative data of cell numbers and TLR staining intensity were compared using Mann–Whitney U tests. Results: Seven COPD patients and nine age-matched HC were analysed. No significant differences in the numbers of inflammatory or epithelial cells in the parenchymal tissue of these groups were observed, although a trend was observed to a reduction in macrophage numbers in the COPD group (median HC=4.2, median COPD=3.2 p=0.17). Similarly, no significant difference was found in the level ofTLR2 or TLR4 expression on any of the cell types examined. However, a trend was observed towards a decrease in TLR2 expression on epithelial cells in the COPD patients (median sMFI 3399 (HC) vs 2462 (COPD), p=0.094). Conclusions: This preliminary analysis has demonstrated that, as hypothesised, there was no significant difference in inflammatory cell load in parenchymal tissue between the two groups. The trend towards a reduced expression of TLR2 in the epithelial cells may reflect an abnormal down regulation of this receptor due to constant exposure to bacterial pathogens. The lack of surveillance of microbial pathogens by TLRs is a potential mechanism by which patients with COPD are more susceptible to infection by new bacterial strains and thus could contribute to exacerbation frequency.